High prevalence of periodontal disease and periodontopathogen colonization in adults with autism spectrum disorder: a pilot study - Berbé, Ludivine; Machouart, Marie; Luc, Amandine; Albuisson, Eliane; Strazielle, Catherine; Bisson, Catherine (Frontiers in Microbiology, 2025)
IntroductionAlteration of the oral microbiome could potentially play a role in the etiology of certain patients with Autism Spectrum Disorder (ASD), similar to the established link between gut microbiota dysbiosis and ASD. Most studies have assessed oral microbiota in children only and few have explored the oral flora composition in adults with ASD.MethodsIn our study, periodontal and dental status was evaluated in 30 adults with ASD using appropriate indices. Oral microbiota samples were collected in crevicular fluid and supra-gingival plaque at inflamed sites in each patient and analyzed using PCR for bacteria and qPCR for protozoa. Demographic data, co-morbidities, medication and oral hygiene habits were also collected.ResultsA total of 86.7% of the patients recruited suffering from severe ASD had periodontal disease and 67% had a high level of supra-gingival plaque. Two major periodontopathogens belonging to the red complex, Treponema denticola and Tannerella forsythia, were both detected in the supra-gingival plaque of 86.2% of patients and in the gingival crevicular fluid of 80 and 86.7% of patients, respectively. Certain microorganisms were statistically more frequently detected in patients with digestive disorders and taking certain medications.DiscussionThe oral microbiota composition of the adults with ASD showed significant differences compared to neurotypical individuals, particularly in the prevalence of the specific microorganisms P. gingivalis, T. tenax and E. gingivalis ST1. The detection frequency of periodontitis and periodontopathogens may have been underestimated due to the lack of cooperation of the adults with ASD during clinical examination and microbiota sampling. Further studies on larger cohorts are needed to consolidate these results to gain a better understanding of variations in oral microbiota.